Pengaruh Efikasi Diri Akademik Terhadap Prestasi Akademik pada Mata Pelajaran Ekonomi - Gutama Dewi Putri; Eka Hendi Andriansyah (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the effect of academic self-efficacy on the academic achievement in economics of grade X and XI students at SMAN 1 Balen in the subject of economics. This study employs a quantitative method with an ex post facto approach. The population used in this study consists of grade X and XI students who take economics classes. The sample size for this study was determined using the Slovin formula with a 5% error rate, resulting in 172 students. The instrument in this study uses a questionnaire statement with a Likert scale to measure the academic self-efficacy variable (X) and academic achievement, which can be seen from the odd semester's Final Summative Assessment (SAS) scores for the 2023/2024 academic year. Data analysis in this study uses simple linear regression analysis by examining the t-test and significance value. Several stages are conducted in this study, including the validity and reliability tests of the statement items, classical assumption tests (normality and linearity tests), and the t-test. The results of this study indicate that the academic self-efficacy variable (X) has a positive effect on the academic achievement in economics of grade X and XI students at SMAN 1 Balen, as shown by the calculated t-value of 8.156, which is greater than the t-table value of 1.973, or a significance level of 0.000 < 0.05, meaning Ho is rejected and Ha is accepted. The influence of academic self-efficacy on academic achievement in economics is quite strong at 53%, while the remaining 47% is influenced by other independent variables. The higher the academic self-efficacy possessed by the students, the higher the academic achievement in economics they will attain, and conversely, if the students' academic self-efficacy is low, their academic achievement in economics will also be low.